Current state and productivity of pine stands in Kharkiv region - Rumіantsev, M. Н.; Vysotska, N. Yu.; Borysenko, O. I.; Yushchyk, V. S.; Khromulіak, O. I. (Forestry and Forest Melioration, 2021)
Introduction Pine stands occupy 33% (about 95 thousand hectares) of the total forest area in the Kharkiv region. They perform important environmental and protective functions. For sound economic management in pine forests, it is necessary to take into account their current state. The aim of the study was to analyse the distribution of pine stands in Kharkiv region in the context of forestry enterprises and natural zones (Forest-Steppe and Steppe) by their origin, the relative density of stocking, growth classes, age groups, site types, and forest categories and to determine main mensuration parameters of pine stands for further development of forest management recommendations. Materials and Methods Forest management materials were used, namely subcompartment inventory database for pine stands as of 01.01.2017. Almost 34 thousand plots where Scots pine is the main species were taken for the analysis. The study covered pine forests within 10 state forest enterprises in Kharkiv region, which are managed by the State Forest Resources Agency of Ukraine. Results In forest enterprises of Kharkiv region, the largest area covered with forest vegetation (287 thousand hectares) is occupied by oak stands – 53%. Pine stands occupy 33% of the total forest area. Most of the pine stands (58%, or 54,834 ha) are concentrated within the steppe zone of the region, the remaining 42% (40,172 ha) grow within the forest-steppe zone. Planted stands predominate, covering 87,605 ha; their proportion reaches 92% of the total area. The proportion of naturally originated stands is 8% (7,401 ha). The age structure of the studied pine stands is unbalanced. Middle-aged stands predominate, making 65% in the pine forests within the forest-steppe part and 56% in those within the steppe part of the region. The forests of Kharkiv region are dominated by pine stands with a density of stocking of 0.7–0.8; their proportion is 73% in the forest-steppe part and 66% in the steppe part. The stands grow according to the I–II growth classes. The proportion of such stands in the total area is 73% among the pine stands in the forest-steppe part and 78% in the steppe part. In the forest-steppe part, the stock of planted pine stands in fresh fairly infertile pine sites reached 432 m3·ha-1, while that of natural ones was 402 m3·ha-1. In fresh infertile pine sites, the stock reached 391 m3·ha-1 for planted pine stands and 387 m3·ha-1 for natural ones. In the steppe part, accordingly, the stock of planted pine stands in fresh fairly infertile pine sites reached 409 m3·ha-1 and that of natural stands was 361 m3·ha-1. In fresh infertile pine sites, the stock of planted pine stands reached 369 m3·ha-1 while for the natural stands it was 344 m3·ha-1. Conclusions Natural and climatic conditions of Kharkiv region are favourable for the successful growth of valuable pine stands since about 76% of such stands in the region grow according to I–II growth classes and almost 70% have a relative density of stocking of 0.7–0.8. However, the age structure of pine stands is unbalanced: middle-aged stands significantly dominate in the area. Pine stands of natural origin have the highest average diameter, height, and stock per 1 ha in comparison with the planted ones both in forest-steppe and steppe parts of the region.